2023
DOI: 10.1029/2023gl103078
|View full text |Cite
|
Sign up to set email alerts
|

No Consistent Simulated Trends in the Atlantic Meridional Overturning Circulation for the Past 6,000 Years

Abstract: The Atlantic Meridional Overturning Circulation (AMOC, Rahmstorf, 2006) is a large-scale ocean circulation that helps transport heat poleward moderating the climate of Europe and eastern North America (Cherchi, 2019). Direct observations of it only became available in 21st century, and show a noticeable weakening (Smeed et al., 2018) that is not captured in full by climate models (Weijer et al., 2020), potentially because it arises from natural variability. Despite this, the IPCC Assessment Report 6 projects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
1
0
0
Order By: Relevance
“…1 b). The AMO cooling trend is in line with a gradual weakening of the AMOC during the Holocene suggested by some studies (Thornalley et al 2018 ; Caesar et al 2021 ; Jomelli et al 2022 ), but at odds with Jiang et al ( 2023 ) who found no consistent trend in overall AMOC strength during the mid-to-late Holocene in an ensemble of nine transient simulations. Furthermore, none of the four simulations have abrupt changes in the AMO at the interannual-to-decadal timescale, although there are multi-centennial modulations in the interannual-to-decadal variability of the AMO that clearly influence WAMR variability (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…1 b). The AMO cooling trend is in line with a gradual weakening of the AMOC during the Holocene suggested by some studies (Thornalley et al 2018 ; Caesar et al 2021 ; Jomelli et al 2022 ), but at odds with Jiang et al ( 2023 ) who found no consistent trend in overall AMOC strength during the mid-to-late Holocene in an ensemble of nine transient simulations. Furthermore, none of the four simulations have abrupt changes in the AMO at the interannual-to-decadal timescale, although there are multi-centennial modulations in the interannual-to-decadal variability of the AMO that clearly influence WAMR variability (Fig.…”
Section: Discussionsupporting
confidence: 69%